Exogenous variables and their influence on domestic credit provision in Nigeria - Chile Nzeh, Innocent (Naše gospodarstvo, 2024)
This article analyses the work-related factors that impact the occurrence of presenteeism in Croatia during the COVID-19 pandemic. The main objective is to examine the connection between key variables and the prevalence of presenteeism among employees in Croatia. The study used logistic regression analysis to examine data from the 2021 European Working Condition Telephone Survey (EWCTS), encompassing a sample of 491 employees from Croatia. The study investigated work-related factors such as job demands, working hours, supervisory responsibilities, telework, and cooperation with coworkers. The analysis also takes into account demographic control variables, including age, gender, and educational level. The findings suggest that there is a significant relationship between work stressors and presenteeism. Employees who lack good collaboration with colleagues are more prone to attending work even when they are unwell. Age was also determined to be a significant factor. The study indicates that work-related factors have an impact on presenteeism in Croatia. To mitigate the adverse effects of presenteeism, firms should adopt strategies to enhance working conditions and foster a conducive work atmosphere. The results offer valuable perspectives for future research and practical strategies to reduce presenteeism and improve employee wellbeing.
Keywords: denarna politika; devizni tečaj; domača posojila; domestic credit; exchange rate; interest rate; kvantilna regresija; monetary policy; obrestna mera; quantile regression